Dose–response effect of Montelukast on post-extraction dental socket repair and skeletal phenotype of mice - Ribeiro, Kim Henderson Carmo [UNESP]; da Silva, Raquel Barroso Parra [UNESP]; Roseno, Ana Carolyna Becher [UNESP]; Barreto, Ana Julia Moreno [UNESP]; Bacelar, Ana Carolina Zucon [UNESP]; Ervolino, Edilson [UNESP]; Duarte, Marco Antônio Húngaro; Fakhouri, Walid D.; Chaves-Neto, Antonio Hernandes [UNESP]; Biguetti, Cláudia Cristina; Matsumoto, Mariza Akemi [UNESP] (Springer Nature, 2023)
Bone metabolism and repair are directly regulated by arachidonic acid metabolites. At present, we analyzed the dose–response effects of a selective cysteinyl leukotriene receptor type-1 antagonist during bone repair after tooth extraction and on non-injured skeleton. Sixty-three 129 Sv/Ev male mice composed the groups: C—Control (saline solution); MTK2—2 mg/Kg of Montelukast (MTK) and MTK4–4 mg/Kg of MTK, daily administered by mouth throughout all experimental periods set at 7, 14, and 21 days post-operative. Dental sockets were analyzed by computed microtomography (microCT), histopathology, and immunohistochemistry. Femurs, L5 vertebra and organs were also removed for observation. Blood was collected for plasma bone and liver markers. Histopathology and microCT analysis revealed early socket repair of MTK2 and MTK4 animals, with significant increased BV/TV at days 14 and 21 compared to C. Higher plasma calcium was detected at days 7 and 21 in MTK4 in comparison to C, while phosphate was significantly increased in MTK2 in the same periods in comparison to C and MTK4. No significant differences were found regarding plasma ALP and TRAP, neither for local TRAP and Runx2 immunolabeling at the healing sockets. Organs did not present histological abnormalities. Increased AST levels have been detected in distinct groups and periods. In general, femur phenotype was improved in MTK treated animals. Collectively, MTK promoted early bone formation after tooth extraction and increased bone quality of femurs and vertebra in a time-dose-dependent manner, and should be considered as an alternative therapy when improved post-extraction socket repair or skeleton preservation is required.
Keywords: 5-Leukotriene; Bone tissue; Cysteinyl leukotrienes; Dental socket; Mice